The Relationship between English Language Proficiency and Intercultural Communication Competence among International Students in a Malaysian Public University - Sarwari, Abdul Qahar; Muhammad Nubli, Abdul Wahab (Universiti Malaysia Pahang, 2016)
Postgraduate students from different nationalities and cultural backgrounds enrol at Malaysian universities to have better learning opportunities, and gain new social and cultural skills. Students may also gain essential competence through their contacts with their peers from different cultures, but some factors may affect their daily interactions. English language is the main means of interactions among international students in Malaysian universities. This study therefore was conducted to examine the relationship between English language proficiency (ELP) and intercultural communication competence among international postgraduate students at a Malaysian public university. A mixed method research design which includes quantitative and qualitative data was employed. Participants were 120 postgraduate students from 17 different countries, in which, 12 participants were interviewed. The findings confirm that ELP is among the main factors that influence interactions among international postgraduate students in a Malaysian public university. The students’ ELP has helped them to have more interactions and improve their intercultural communication competence. The results also illustrate that daily interactions have helped the students to improve their ELP and discover new strategies to deal with different linguistic and communicative challenges while they are in a multicultural collegiate environment.